Level Of Understanding And Implementation Of Service Excellent By Academic Community: A Study Of Pharmacy Lecturers At STIKES Kendal - Utami, Lucky Restyanti Wahyu; Utami, Rose Malinda Andamari Wahyu; Utomo, Slamet (Jurnal Ilmiah Wahana Pendidikan, 2026)
Service excellent in education is considered crucial, especially for producing high-quality graduates who can provide the best service to customers when they enter the community. The purpose of this study was to determine the level of understanding and implementation of service excellent among the academic community, particularly among pharmacy lecturers at STIKES Kendal. The research used was quantitative. The study was conducted with D3 and S1 pharmacy lecturers at STIKES Kendal who were willing and met the inclusion criteria as respondents. The study used an electronic questionnaire in the form of a Google Form. The level of understanding and level of implementation of good service excellent among D3 pharmacy lecturers and S1 pharmacy lecturers at STIKES Kendal is very good, this is shown by the results of the research questionnaire which shows a percentage of 100%. Although the level of understanding and implementation of service excellent among D3 and S1 pharmacy lecturers at STIKES Kendal is very good, this study does not yet demonstrate the impact of the service excellent provided by these educators on students. Therefore, suggestions for future research are expected to examine how students perceive the service excellent provided by pharmacy lecturers during their learning process while studying at university.